Cervical spondylomyelopathy in dogs - MOUZAKITIS (Η.Ν. ΜΟΥΖΑΚΙΤΗΣ), E. N.; KAZAKOS (Γ.Μ. ΚΑΖΑΚΟΣ), G. M.; PATSIKAS (Μ.Ν. ΠΑΤΣΙΚΑΣ), M. N.; POLIZOPOULOU (Ζ.Σ. ΠΟΛΥΖΟΠΟΥΛΟΥ), Z. S. (Journal of the Hellenic Veterinary Medical Society, 2017)
Cervical spondylomyelopathy (CSM) is the most common disease of the cervical spine in large and giant breed dogs. Its exact aetiology is not known and the relevant pathophysiology is not clear; two clinical entities are currently recognised: disc-associated and osseous-associated spinal cord compression. History and clinical signs are indicative of cervical spondylomyelopathy, although its neurologic manifestation can vary from cervical pain only to tetraparesis and respiratory compromise. Imaging of the spine is fundamental for definitive diagnosis and includes radiography, myelography, computed tomography and magnetic resonance imaging. It is also the cornerstone of surgical planning. This is usually based on the subjective concept of dynamic or static compressive lesions. Among the advanced imaging techniques, magnetic resonance imaging is superior to myelography for diagnosis of cervical spondylomyelopathy, although, at present, these techniques can be considered complementary. Furthermore, attention is drawn to the false positive interpretations of magnetic resonance findings, which are related to clinically irrelevant spinal cord compression. Hence, the degree of agreement between neuroanatomic localization and neuroimaging is of the outmost importance. Conservative treatment consists of strict restriction of the animal and the use of steroid or non-steroid anti-inflammatory drugs. Objective of surgical treatment is to decompress the spinal cord. However, the decision-making process of surgical treatment is more complicated, because a large number of different surgical techniques have been proposed. Adjacent segment disease is a controversial complication of the surgical treatment of disk-associated cervical spondylomyelopathy and recently introduced motion-preserving techniques are targeted on reducing its occurrence. Significant prognostic information for focal parenchymal damage may derive from magnetic resonance imaging studies, but this remains to be further clarified.